Low-carbon preparation of blast furnace burden from iron ore concentrates via cold-bonding process: New insights into the effect of concentrate type - Xiaolong Wang; Zhiyun Ji; Xiaohui Fan; Min Gan; Shaochun Li; Shengxuan Fan; Zengqing Sun; Jiaming Lv; Yanqing Du; Jiasheng Li; Ying Yu (Minerals Engineering, 2026)

Oxidative-stress-mediated apoptosis triggered by microplastics disrupts bovine oocyte maturation - Yu Wang; Jiaming Yue; Yijing Yin; Yan Zhang; Yi Zheng; Hao Jiang; Jiabao Zhang; Bao Yuan; Liang Shuang (Theriogenology, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Efficient one-pot lactic acid production from cellulose via a Trichoderma reesei and Bacillus coagulans cooperation leveraging substrate-induced secretomes - Shuai Liang; Chang Yu; Jiaming Fu; Yuanming Tao; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2026)

Amphibian skin peptides: Diversity, biological functions, and research progress - Zihui Chen; Qing Pan; Jiaming Zhang; Ren Lai; Wenhua Yu; Aili Wang (Toxicon, 2026)

Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

Multi-source accumulation pathways and drivers of soil organic carbon in coastal saltmarsh wetlands - Rui Zhong; Jiaming Yao; Lijie Pu; Jiayi Xie; Jiawei Tao; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Limin Yu; Gaili He; Sihua Huang (CATENA, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

Components with potential anti-inflammatory effect from the seeds of Dolichos lablab - Wei Zhang; Yijin Wu; Jiaming Cheng; Jingya Ruan; Yingying Wang; Lequan Yu; Dan Wang; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2026)

Development of an indirect ELISA and an immunochromatographic test method for early detection of Haemonchus contortus infection in sheep - Xueqiu Chen; Lingyun Mou; Manqin Deng; Jingju Zhang; Jiaming Yu; Jianfang Li; Hongli Zhang; Guangxu Ma; Yi Yang; Aifang Du (Veterinary Parasitology, 2026)

The dual roles of dissolved organic matter as a source and sink of hydroxyl radicals in the photodegradation of carbamazepine in liquid water and ice - Caihong Jiang; Jiaming Chen; Meng Yuan; Shuang Xue; Yingzi Lin; Yingtan Yu (Process Safety and Environmental Protection, 2026)

Structural properties of two glycans in the fruits of jujube and their regulation effect of M1-type and M2-type macrophage - Jingya Ruan; Ping Zhang; Jiaming Cheng; Lequan Yu; Yijin Wu; Yinuo Zheng; Yi Zhang; Tao Wang (Carbohydrate Polymers, 2026)

Uniaxial compressive behavior of frozen silty clay at extreme low temperature with varying initial water content - Jiaming Xian; Wansheng Pei; Yuanming Lai; Mingyi Zhang; Fan Yu; Yanyan Chen (Cold Regions Science and Technology, 2026)

Rapid Visual Detection of Decapod Iridescent Virus 1 ( DIV1 ) by RPA Combined With LFS - Quanling Mu; Cunbao Ding; Ying Xie; Xi Zhen; Xianrui Wang; Tongaobo Qi; Jiaming Zhang; Yakun Yu (Journal of Fish Diseases, 2026)
Decapod iridescent virus 1 (DIV1) causes severe disease outbreaks in shrimp and crab culture areas. A simple, rapid, and visual DIV1 assay is important for the control of viral diseases. This study presented a novel DIV1 detection method that combines recombinase polymerase amplification (RPA) and lateral flow strip (LFS). After selecting primers and probes, we optimised the concentration of the reverse primers, reaction time, as well as reaction temperature of RPA‐LFS detection. RPA can amplify the target gene within 18 min at a constant temperature of 38°C, and LFS can observe the amplification results within 3 min. Importantly, there is no cross‐reactivity with other infectable shrimp viruses and pathogens, such as WSSV, IHHNV, TSV, EHP, CMNV, YHV, MrNV samples, as well as Vp AHPND . In addition, RPA‐LFS has high detection sensitivity, with a lower detection limit of 1.12 × 10 1 copies/μL. Using 110 field samples, the results of qPCR recommended by WOAH (OIE) and RPA‐LFS were identical, indicating that RPA‐LFS is as reliable as qPCR. The RPA‐LFS assay is a valuable tool for the rapid and accurate detection of DIV1.

Synergistic layer engineering for high-efficiency blue emission in pure-bromide quasi-2D perovskite light-emitting diodes - Jiaming Yu; Bochao Jia; Shuguang Zhang; Yachun Guo; Yue Liang; Jiangshan Chen; Linfeng Lan; Junbiao Peng (Chemical Engineering Journal, 2026)

Br radicals generated via bromate-free photoactivation may promote degradation of emerging contaminants in highly saline waters - Min Zhao; Jiaming Gan; Yingdong Li; Mingbao Feng; Hamid Mohammed Al-Gabr; Xin Yu; Lei Wang (Water Research, 2026)

Evaluating aeration rate modulation to restructure denitrifier communities for nitrous oxide mitigation in cattle manure composting using a novel integrated analytical framework - Yu Sun; Xiran Zhou; Jiaming Fan; Lei Sun; Shuai Shi; Xiuhong Xu (Journal of Environmental Management, 2026)

Unlocking ultrahigh anion adsorption in sunlight-responsive metal-organic frameworks for water purification - Xu Wu; Qian Guan; Mengyu Tang; Yilei Fang; Jiaming Gan; Xinyu Zhang; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

Spatial-interaction-context and temporal-attention U-Net model for spatio-temporal prediction of Sea Surface Temperature field - Jiaming Ma; Jun Song; Junru Guo; Yanzhao Fu; Yu Cai; Yuan Zhang; Jie Tian; Ming Li (Regional Studies in Marine Science, 2025)

Nonlinear relationship between built environment and commute mode choice: A comparison of commuters within and beyond the long commute threshold - Ming Yu; Zhaomin Tong; Jiaming Yang; Yanchi Lu; Yang Liu; Yanfang Liu; Yaolin Liu (Journal of Transport Geography, 2025)

Thermophilic antagonistic/competitive networks drive low nitrogen loss in Phase I commercial composting: Deciphering microbe-nitrogen coupling using the novel multistep interaction validation analysis - Yu Sun; Jiaming Fan; Yue Zhang; Zhaoxue Gai; Shuai Shi; Xiuhong Xu (Journal of Environmental Chemical Engineering, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Can we improve well‐being while reducing carbon emissions? Household‐level evidence from China - Jiaming Yu; Wenling Liu; Xiaoyan Meng; Xinzhu Zheng (Journal of Industrial Ecology, 2025)
Understanding the link between well‐being and carbon emissions is crucial, as demand‐side emission reduction efforts should not compromise living standards. While a nonlinear, threshold‐based relationship between well‐being and carbon emissions has been identified at the national level, empirical evidence at the household or individual level remains limited. Using data from the China Family Panel Studies, this study develops a multidimensional indicator framework to measure household well‐being and empirically assesses its relationship with per capita carbon emissions. The results indicate an inverted U‐shaped relationship, where carbon emissions are initially associated with improvements in well‐being. However, beyond a certain threshold, further increases in carbon emissions are no longer linked to significant gains in well‐being. Specifically, the decoupling threshold is estimated at 15.4 tons of CO 2 annually per capita in the absence of technological progress, and is reduced to 9.7 tons when technological improvements are taken into account. However, the available carbon budget is insufficient for all individuals to reach these decoupling points, and sample households could only reduce emissions by 1.4% without sacrificing overall well‐being. Moreover, prioritizing limited carbon allowances for low‐income groups may maximize societal well‐being, since their carbon intensity of human well‐being is comparatively lower. These findings underscore the importance of technological progress and population heterogeneity in designing fair and effective policies that balance well‐being with emission reductions.

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Highly selective aerobic oxidation of polystyrene to benzoic acid catalyzed by nitrogen dioxide - Yunkai Yu; Yue Zhu; Jiaming Liu; Minghao Zhang; Jing Li; Shicheng Zhang; Qingqing Mei (Science Bulletin, 2025)

Dynamic optimization of cooling temperature setpoints in multiple thermal zones of office buildings in connection with D3QN - Ben Jiang; Jiaming Wang; Yu Li; Peng Wang; Yacine Rezgui; Chengyu Zhang; Menglin Ding; Liuyang Shangguan; Tianyi Zhao (Energy and Buildings, 2025)

Extraction of Chlorella polysaccharide using natural deep eutectic solvent - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Huiqing Zhang; Changhua Shang (Algal Research, 2025)

Purification and characterization of cellulase produced by Bacillus sp. HMM - Lanqian Huang; Lei Mo; Jiaming Jiang; Yu Huo; Shisong Yu; Jianmei Ou; Siyu Liu; Xinyu Xie; Guyu Yan; Chuzun Liao; Shangxin Wu; Huiqing Zhang; et al. (Antonie van Leeuwenhoek, 2025)

Insight of multi-polarization effect by constructing high-entropy spinel ferrite/perovskite @ amorphous carbon for enhancing electromagnetic wave absorption - Xinyang Liu; Zhekai Zhang; Fengyu Wu; Fenyang Tian; Jie Sheng; Menggang Li; Jiaming Li; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2025)

Extraction, purification and antioxidant activity of Chlorella polysaccharide - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Changhua Shang (Algal Research, 2025)

Sensor fault diagnosis and calibration based on voting mechanism for online application using virtual in-situ calibration and time series prediction - Jiteng Li; Jiaming Wang; Peng Wang; Sungmin Yoon; Yu Li; Yacine Rezgui; Yuxin Li; Tianyi Zhao (Building and Environment, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Phytoextraction of Soil Cadmium by Vetiveria zizanioides Dead Shoots - Wenwen Li; Ning Liu; Xiaoling Tan; Ruoyao Shen; Jiaming Yu; Jie Li; Khateeb Hussain; Shiyong Yang (Bulletin of Environmental Contamination and Toxicology, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Highly stable anode-free solid-state sodium batteries enabled by electrostatic shielding and nitrogenated interphase - Wuliang Feng; Caixia Li; Peiyao Wang; Jiaming Hu; Xuan Yu; Ying Zhang; Xingbao Zhu; Dengsong Zhang; Yongyao Xia; Yufeng Zhao (Chemical Engineering Journal, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Efficient extraction of Spirulina phycocyanin using natural deep eutectic solvents and its characteristics - Juying Lin; Jiaming Jiang; Lei Mo; Yu Huo; Yan Pang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Acoustic micromixing in a serpentine channel with sharp teeth for controllable nanomaterial synthesis - Bin Ran; Bo Liu; Chaozhan Chen; Wenqiang Tong; Jiaming Shi; Jiaxi Du; Zhihang Yu; Siwei Bai; Huaying Chen; Yonggang Zhu (Chemical Engineering Journal, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

Extraction, purification and characterization of Spirulina phycocyanin - Juying Lin; Yan Pang; Yu Huo; Jiaming Jiang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Efficient depolymerization of lactic acid oligomers into lactide with low racemization - Jiaming Yu; Ting Li; Qifeng Wei; Xiulian Ren (Journal of Environmental Chemical Engineering, 2024)

Can wood harvest followed by forest regrowth enhance carbon sequestration of the forest sector in China? - Mengyu Wang; Chao Yue; Junhao He; Pengyi Zhang; Mengyang Xu; Yu Li; Jiaming Wang; Lele Wang; Can Xu (Global and Planetary Change, 2024)

Environmentally friendly recycling of energy storage functional materials from hazardous waste lithium-containing aluminum electrolytes - Jiaxin Yang; Wenju Tao; Jiaming Li; Lingyu Kong; Shaohua Wu; Jingui He; Zhaoshun Liu; Yu Sun; Chao Fan; Zhaowen Wang (Chemical Engineering Journal, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Whole genome sequencing and analysis of Bacillus sp. TTMP2, a tetramethylpyrazine-producing bacterium - Shanling Gan; Lingru Ruan; Xinyi Xu; Lirong Luo; Yu Huo; Jiaming Jiang; Xiumin Zhang; Changhua Shang (Molecular Biology Reports, 2024)

A strategy for treatment of low-grade ore: Efficient separation and purification of iron - Shishun Dong; Ting Li; Jiaming Yu; Qifeng Wei; Xiulian Ren (Process Safety and Environmental Protection, 2024)

Construction of La1−xSrxNiO3/g-C3N4 type-Z heterojunctions with enhanced visible-light photocatalytic degradation of organic pollutants - Pengke Yu; Jiaxing Guo; Liang Guo; Yaqin Deng; Juntao Tan; Qunang Xu; Qingmao Zhang; Jiaming Li (Environmental Research, 2024)

Building block design of thermally regenerable metal–organic framework composites for highly selective lithium adsorption - Xinyu Zhang; Xu Wu; Jiaming Gan; Xin Yu; Huanting Wang; Ranwen Ou (Chemical Engineering Journal, 2024)

Regulatory mechanisms of miR171d–SCL6 module in the rooting process of Acer rubrum L. - Huiju Li; Jiayu Yu; Jiaming Qin; Hewen Zhao; Kezhong Zhang; Wei Ge (Planta, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

Comparative study on dynamic responses of integrated installation process of a 5-MW and a 15-MW offshore wind turbine considering a pre-installed foundation - Jiaming Liu; Zhongming Xiao; Kai Wang; Shuo Huang; Yu Du (Ocean Engineering, 2024)

Transporters and phytohormones analysis reveals differential regulation of ryegrass (Lolium perenne L.) in response to cadmium and arsenic stresses - Wenwen Li; Jie Li; Khateeb Hussain; Kaihao Peng; Jiaming Yu; Miaoqing Xu; Shiyong Yang (Journal of Hazardous Materials, 2024)

Biochar reduces gaseous emissions during poultry manure composting: Evidence from the evolution of associated functional genes - Ruijing Dang; Yu Cai; Jiaming Li; Yilin Kong; Tao Jiang; Jiali Chang; Sheng Yao; Jing Yuan; Guoxue Li; Guoying Wang (Journal of Cleaner Production, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Aggregation, retention and transport of γ-MnO2 nanoparticles in water-saturated porous media: Impact on the immobility of thallium - Jiaming Luo; Dafeng Cai; Lezhang Wei; Hang Shi; Yu Liu; Haiqi Yan; Dinggui Luo; Tangfu Xiao; Xuexia Huang; Qihang Wu (Environmental Pollution, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Carbon emissions and low-carbon development in Olefin industry - Qun Shen; Jiaming Gu; Li Shang; Shuang Liu; Xuehang Song; Weisheng Yu; Yongping Liu; Nannan Sun; Wei Wei (Environmental Research, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Kinetic modeling and mechanisms of parahalogenated phenols degradation by UV222/H2O2 - Min Zhao; Ting Li; Yizhan Zhang; Jiaming Gan; Yiting Zhao; Xin Yu; Lei Wang (Journal of Cleaner Production, 2024)

Electro-enhanced metal-free peroxymonosulfate activator coupled with membrane-assisted process for simultaneous Ni-EDTA decomplexation and Ni ions recovery - Jiaming Zhang; Chao Yu; Longqian Xu; Zhenyu Zhao; Deli Wu (Chemosphere, 2023)

Discrete solutions and interaction dynamics for coupled nonlocal discrete nonlinear Schrödinger equations in an inhomogeneous optical fiber - Li Li; Fajun Yu; Jiaming Yu (Wave Motion, 2023)

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

Multi-objective shape optimization of autonomous underwater vehicle by coupling CFD simulation with genetic algorithm - Xiaodong Chen; Liang Yu; Leo Yang Liu; Lele Yang; Shunyuan Xu; Jiaming Wu (Ocean Engineering, 2023)

Responses of sediment nitrogen forms and bacterial communities to different aquatic nitrogen conditions in three submerged macrophyte-type ecological treatment systems - Xinyan Zhou; Tiehan Cheng; Jiaming Yu; Mengting Sheng; Xuelian Ma; Yucheng Cao (Environmental Research, 2023)

Rapid adaptive evolution of Bacillus coagulans to undetoxified corncob hydrolysates for lactic acid production and new insights into its high phenolic degradation - Jiaming Fu; Zijie Wang; Hongcheng Miao; Chang Yu; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2023)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

Superiority of UV222 radiation by in situ aquatic electrode KrCl excimer in disinfecting waterborne pathogens: Mechanism and efficacy - Ting Li; Yizhan Zhang; Jiaming Gan; Xin Yu; Lei Wang (Journal of Hazardous Materials, 2023)

Quality retention and delay postharvest senescence of figs (Ficus carica L.) using 1-methylcyclopropene and modified atmosphere packaging during cold storage - Cailian Wang; Jiaming Du; Dehua Hou; Xiaohong Guo; Qianting Liu; Linwen Liu; Yu Fang; Liping Kou (Food Bioscience, 2023)

Effect of gastrodin against cognitive impairment and neurodegeneration in APP/PS1 mice via regulating gut microbiota–gut–brain axis - Yuhe Zhang; Yan Chen; Shushu Yuan; Qingxia Yu; Jianjiong Fu; Luyun Chen; Jiaming Liu; Yuping He (Experimental Brain Research, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Preparation of a novel metal-free polypyrrole-red phosphorus adsorbent for efficient removal of Cr(VI) from aqueous solution - Longyu Qiu; Yingjun Wang; Rui Sui; Chenxi Zhu; Weiwei Yang; Yongsheng Yu; Jiaming Li (Environmental Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Experimental investigation on pressure oscillation induced by steam injection into subcooled water through an opposite nozzle - Haitao Ren; Dingding Liang; Tao Lu; Jie Wang; Pei Yu; Jie Li; Jiaming Zhao; Ping Xiong (Annals of Nuclear Energy, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Optimization of a compact on-site stormwater runoff treatment system: Process performance and reactor design - Yangjie Qin; Chuanting Zhou; Siqi Yu; Hongjian Pang; Jiaming Guo; Jun Wei; Libing Wang; Yunxin Xing; Ying An; Zhen Zhou (Chemosphere, 2023)

Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength - Yu Cao; Chengxue Ma; Jinni Yao; Wanpeng Chen; Li Gu; Hongxia Liu; Caihong Liu; Jiaming Xiong; Xiaoliu Huangfu (Chemosphere, 2023)

Mechanisms of PiT2-loop7 Missense Mutations Induced Pi Dyshomeostasis - Hao Sun; Xuan Xu; Junyu Luo; Tingbin Ma; Jiaming Cui; Mugen Liu; Bo Xiong; Shujia Zhu; Jing-Yu Liu (Neuroscience Bulletin, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Occurrence and driving forces of different nitrogen forms in the sediments of the grass and algae-type zones of Taihu Lake - Zihan Zhao; Mingli Zhang; Jiaming Tian; Kangkang Yu; Yan Chen; Yanhua Wang (Environmental Science and Pollution Research, 2022)

HIV Tat Protein Induces Myocardial Fibrosis Through TGF-β1-CTGF Signaling Cascade: A Potential Mechanism of HIV Infection-Related Cardiac Manifestations - Yannan Jiang; Lu Chai; Hongguang Wang; Xiuyun Shen; Moyondafoluwa Blessing Fasae; Jinfeng Jiao; Yahan Yu; Jiaming Ju; Bing Liu; Yunlong Bai (Cardiovascular Toxicology, 2021)

Effects of High-Dose of Copper Amino Acid Complex on Laying Performance, Hematological and Biochemical Parameters, Organ Index, and Histopathology in Laying Hens - Qin Zhou; Jiaming Zhu; Bing Liu; Jialing Qiu; Xintao Lu; Brian Curtin; Fei Ji; Dongyou Yu (Biological Trace Element Research, 2021)

Important progress and future prospects for studies on urban public recreational space in China - Ling Yu; Jiaming Liu; Tao Li (Journal of Geographical Sciences, 2019)

Identification and classification of resource-based cities in China - Jianhui Yu; Jiaming Li; Wenzhong Zhang (Journal of Geographical Sciences, 2019)

International symposiums on urbanization and planning in China and India, organized by the delegation of the Geographical Society of China - Yu Yang; Jiaming Li (Journal of Geographical Sciences, 2017)

Small RNA changes in synthetic Brassica napus - Ying Fu; Meili Xiao; Huasheng Yu; Annaliese S. Mason; Jiaming Yin; Jiana Li; Dongqing Zhang; Donghui Fu (Planta, 2016)

Stacking S5-n and f5-n to overcome sterility in indica–japonica hybrid rice - Jiaming Mi; Guangwei Li; Jianyan Huang; Huihui Yu; Fasong Zhou; Qifa Zhang; Yidan Ouyang; Tongmin Mou (Theoretical and Applied Genetics, 2016)

Industrial spatial agglomeration using distance-based approach in Beijing, China - Jiaming Li; Wenzhong Zhang; Jianhui Yu; Hongxia Chen (Chinese Geographical Science, 2015)

Study on the synergy between intra-urban resident’s migration and job change in Beijing - Jianhui Yu; Guanpeng Dong; Wenzhong Zhang; Jiaming Li (Journal of Geographical Sciences, 2015)